2020
DOI: 10.29408/veles.v4i1.1994
|View full text |Cite
|
Sign up to set email alerts
|

Implementing of Academic Text in Advanced Grammar Learning

Abstract: Grammar has the main role in English language learning. It can be given an impact on English language skill mastery. The purposes of this study were to find deeply comprehending on grammar mastery using academic text. The method of study used a one-group experimental design. The sample was 25 students in the English Language Program at Universitas Indraprasta Jakarta. The sample was taken using purposive sampling. Essay test and observation technique were the instruments used in collecting the data. The data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…Their findings revealed that after only four courses employing this method, more than half of the students could name 16 tenses and construct sentences in various forms, indicating that the pupils had improved. It also agreed with research by Baron (2020) and Kaharuddin (2022), which found that teaching grammar directly produced somewhat superior results.…”
Section: Table 1 Paired Samples Test Of the Explicit Grammar Teaching...supporting
confidence: 90%
See 1 more Smart Citation
“…Their findings revealed that after only four courses employing this method, more than half of the students could name 16 tenses and construct sentences in various forms, indicating that the pupils had improved. It also agreed with research by Baron (2020) and Kaharuddin (2022), which found that teaching grammar directly produced somewhat superior results.…”
Section: Table 1 Paired Samples Test Of the Explicit Grammar Teaching...supporting
confidence: 90%
“…More than half of the students were able to identify 16 tenses and construct sentences in various forms. Moreover, Baron (2020) conducted a study involving 25 university students in Jakarta to compare direct and indirect methods of teaching grammar from academic texts. The results revealed that teaching grammar directly was slightly more effective, although the difference was not significant.…”
Section: Introductionmentioning
confidence: 99%